The Effect of Group Savings on the Household Welfare in Uganda: A Case Study of Bataka Abamwe Group in Butogota Town Council, Kanungu District. - Akancungura, Sheila (Kabale University, 2023)
The study examined the effect of group savings on household welfare in Uganda. A case study of Bataka Abamwe group in Butogota Town Council, Kanungu district Uganda. The study used 133 respondents and a sample size. The study used a descriptive research design based on qualitative and quantitative approaches to get a better analysis of the study. Both primary and secondary data collection tools were used with relevant tools like questionnaires to come up with the required data. In the findings, it was established that savings groups improve overall income or livelihoods. People's savings are not only used for consumption but also it's invested in businesses like agriculture that later will be harvested hence increasing the overall income or livelihood and this makes people to send their children to good schools to attain good levels of education. From the findings, some respondents responded that the most important role of adult, female participants in household and communities is decision-making. Most respondents replied yes on how savings help people to cope with shocks, manage emergencies, and increase resilience. The study concludes that savings groups improve overall income or livelihoods for improved education. Implying that those households who are not involved in group savings may not have improved education. Since people's savings are not only used for consumption but also it's invested in businesses like agriculture that later will be harvested and hence increasing the overall income or livelihood and this makes people to send their children to good schools to attain good levels of education. The study recommends that Due to the increasing growing gap between the males and females in terms of income distribution. Benefits, responsibility and power there is need to embark on promotion of gender equality in order to promote equity and also increase the role played by the females in these projects in order thus combating the problem of male domination and influence at the expense of the females. The government through the ministry of gender, labor and social development should support community groups by providing funds informs of livelihood support, savings funds to enable community groups become independent in such a way that they can operate and become sustainable on their own. This will help to ensure continuity of these groups.